Photoelectrochemical cells with a pyridine-anchored organic dye photoanode for efficient H2 generation by water reduction - Tang, Kun; Shao, Jiang-Yang; Zhong, Yu-Wu (Chemical communications (Cambridge, England), 2023)
TiO2 photoelectrodes modified with organic dyes with pyridine anchoring groups are prepared, which are used as photoanodes of dye-sensitized photoelectrochemical cells for efficient water reduction with high photocurrent density and stability in aqueous solutions. Vigorous H-2 generation with a production rate of around 250 mu mol h(-1) is realized with a photoanode of an active area of 5 x 5 cm(2).